Lucy by the sea : a novel - Strout, Elizabeth (Strout, Elizabeth. Amgash, 2022)
"With her trademark spare, crystalline prose-a voice infused with "intimate, fragile, desperate humanness" (The Washington Post)-Elizabeth Strout once again turns her exquisitely-tuned eye to the inner workings of the human heart, this time following the indomitable heroine of My Name Is Lucy Barton and Oh William! through the early days of the pandemic. As a panicked world goes into lockdown, Lucy Barton is uprooted from her life in Manhattan and bundled away to a small town in Maine by her ex-husband and longtime friend, William. For the next several months, it's just Lucy, William, and their complex past together in a little house nestled against the moody, swirling sea. They will not emerge unscathed"--